Enantioselective rearrangement of exo-norbornene oxide to nortricyclanol - Hodgson, D; Wisedale, R (1996)
The enantioselective α-deprotonation-rearrangement of exo-norbornene oxide 1 to (-)-nortricyclanol 2 in up to 52% ee using a nonracemic lithium amide, or an organolithium in the presence of (-)-sparteine, is described.